2022
DOI: 10.1111/jcpe.13587
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial to investigate the effect of dietary protein sources on periodontal health

Abstract: Aim: The aim was to assess two macronutrient interventions in a 2 Â 2 factorial dietary design to determine their effects on oral health.Materials and Methods: Participants (65-75 years old) with a body mass index between 20 and 35 kg/m 2 of a larger randomized control trial who consented to an oral health assessment were recruited. They had ad libitum access to one of four experimental diets (omnivorous higher fat or higher carbohydrate, semi-vegetarian higher fat or higher carbohydrate) for 4 weeks. The peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…A cross-sectional study conducted in Denmark suggested an inverse relationship between casein and whey protein intake and periodontitis in adults [ 171 ]. Additionally, a randomised controlled study demonstrated that a higher-fat, semi-vegetarian diet is protective against clinical parameters of periodontitis in healthy adults aged 65–75 years [ 172 ]. In a cross-sectional study, vegetarians aged ~40 years had smaller pocket depth, and less bleeding on probing, compared to non-vegetarians [ 173 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study conducted in Denmark suggested an inverse relationship between casein and whey protein intake and periodontitis in adults [ 171 ]. Additionally, a randomised controlled study demonstrated that a higher-fat, semi-vegetarian diet is protective against clinical parameters of periodontitis in healthy adults aged 65–75 years [ 172 ]. In a cross-sectional study, vegetarians aged ~40 years had smaller pocket depth, and less bleeding on probing, compared to non-vegetarians [ 173 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence supporting a strong association between periodontitis and micronutrient intake [49][50][51][52][53][54][55]. Varied studies have been conducted in different directions to evaluate the association between periodontitis and micronutrient intake [45,[56][57][58][59][60]. Existing studies tend to explore the correlation using linear models, showing that associations between micronutrient intake and some other diseases were complex and nonlinear [61][62][63][64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%
“…Persons who maintained a normal weight, performed the recommended level of exercise, and ate a high-quality diet were 40% less likely to have periodontitis than those who did not engage in any of these health-promoting behaviors [ 154 ]. Regarding the dietary content, a study in which subjects consumed four experimental diets (omnivorous higher fat or higher carbohydrate, semi-vegetarian higher fat or higher carbohydrate) found that the semi-vegetarian higher fat group showed improved CAL and decreased gingival crevicular fluid volume after the follow-up period [ 155 ]. These studies indicate that lifestyle habits such as an appropriate low-calorie, vegetable-rich diet and moderate exercise can have a positive impact on periodontal tissue health.…”
Section: Next-generation Procedures In Periodontal Diseasementioning
confidence: 99%